Aquinas on Connaturality and Education - MOONEY, T. Brian (Institutional Knowledge at Singapore Management University, 2012)
Connatural knowledge is knowledge readily acquired by beings possessing a certain nature. For instance, dogs have knowledge of a scent-world exceeding that of human beings, not because humans lack noses, but because dogs are by nature better suited to process olfaction. As various ethicists have argued, possession of the virtues involves a sort of connatural knowing. Here, connatural knowledge emerges as a knowledge by inclination which systematically tracks the specific moral interests we humans possess precisely because we are human. In this essay we explore the importance of connaturality for moral education.